Playing Percussion to Develop Physical-Motor and Emotional Skills of a Cerebral Palsy Child - Nur Wulan, Gytta Ayu; Deliana, Sri Maryati; Sugiyo Pranoto, Yuli Kurniawati (Journal of Primary Education, 2021)
Cerebral palsy is derived from a word â€œcerebralâ€, meaning a brain, and â€œpalsyâ€, meaning disability. Cerebral palsy is a disability condition influencing movements and body positions of an individual. This research aims to analyze the influence of physical-motor and emotional skills of a child with cerebral palsy at before, during, and after being intervened to play percussion. This research is a single-subject experimental research. The finding showed that playing percussion was proven able to improve the physical-motor and emotional skills of a cerebral palsy child. The average result on baseline 1 period, done within 5 sessions, was 38%. It improved during the intervention period that was done during 5 sessions. It was 61%. The improvement could be seen on the baseline 2, done within 6 sessions. It was 77.5%. Therefore, there was significant improvement between before and after intervention with 39.5%. This research is expected to be the basic research in developing instruments to develop learning or skills for a cerebral palsy child.